The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1037/0894-4105.16.2.254
|View full text |Cite
|
Sign up to set email alerts
|

The apolipoprotein E gene, attention, and brain function.

Abstract: The ɛ4 allele of the apolipoprotein E (ApoE) gene is associated with alterations in brain function and is a risk factor for Alzheimer's disease (AD). Changes in components of visuospatial attention with ApoE-ɛ4, aging, and AD are described. Healthy middle-aged adults without dementia who have the ApoE-ɛ4 gene show deficits in spatial attention and working memory that are qualitatively similar to those seen in clinically diagnosed AD patients. The findings support an association between ApoE polymorphism and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
96
3
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 215 publications
(371 reference statements)
5
96
3
1
Order By: Relevance
“…As AD usually appears later in life and progresses slowly, the APOE 4 allele may exert its effect prior to the clinical diagnosis of AD. Studies using information-processing approaches to dissect cognition into component operations found impairments in attention and working memory in individual carriers of the APOE 4 gene [13,24]. These changes were found in healthy middleaged adults in their 50s who were clinically without dementia.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…As AD usually appears later in life and progresses slowly, the APOE 4 allele may exert its effect prior to the clinical diagnosis of AD. Studies using information-processing approaches to dissect cognition into component operations found impairments in attention and working memory in individual carriers of the APOE 4 gene [13,24]. These changes were found in healthy middleaged adults in their 50s who were clinically without dementia.…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have shown a relatively selective effect of the 4 allele on episodic memory [32,35] and attention [24], especially in the early stages of the disease. A cognitive phenotype characterized by memory and verbal comprehension deficits has been claimed for APOE 4 homozygotes with AD as well as those with mild cognitive impairment [32].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, evidence supporting the role of APOE ε4 allele as a risk factor for development of AD has accumulated (2). Furthermore, it has been reported that the ε4 allele contributes in age-related cognitive decline (3,4) and functional (5) and structural (6) brain changes of middle-age healthy ε4 carriers. In particular, functional studies using positron emission tomography (PET) have provided evidence of reduced glucose metabolism rate in prefrontal, posterior cingulated, and parietotemporal regions of young (7) and late middle aged (8) cognitively normal APOE ε4 carriers.…”
mentioning
confidence: 99%
“…One area of cognition that has shown promise as a preclinical marker of AD in elderly individuals with the ApoE-e4 allele is attention and working memory. Specifically, some studies have found that nondemented elderly with the e4 genotype show subtle deficits on neuropsychological tests that have strong attentional demands, such as the Digit Span subtest (Albert, Moss, Tanzi, & Jones, 2001;Caselli et al, 1999;Caselli et al, 2001;Linn et al, 1995;Wilson et al, 2002); WMS-R Mental Control subtest (Tierney et al, 1996), Operation Span Test (Rosen, Bergeson, Putnam, Harwell, & Sunderland, 2002), Digit Symbol subtest (Masur, Sliwinski, Lipton, Blau, et al, 1994;Yaffe, Cauley, Sands, & Browner, 1997), attentional switching and disengagement (Greenwood, Sunderland, Friz, & Parasuraman, 2000;Parasuraman, Greenwood, & Sunderland, 2002), and supra-span ability and divided attention (Rosen et al, 2002). However, several other studies have failed to replicate findings of attentional deficits in nondemented e4 elderly groups (Baeckman, Small, & Fratiglioni, 2001;Elias et al, 2000;Flory, Manuck, Ferrell, Ryan, & Muldoon, 2000;Smith et al, 1998).…”
Section: Introductionmentioning
confidence: 99%